Paradoxically ME (Existential Analysis: Journal of the Society for Existential Analysis, 2022)
Finding one's identity as someone belonging to two cultures and two nations can be a lifetime struggle. Defining who we are and trying to embrace the widest version of our being is not easy. The polarities are everchanging, as life takes its course.
Keywords: Identity; foreign-ness; language; bilingualism; belonging; home